PERLINDUNGAN HUKUM TERHADAP PEKERJA PADA BADAN USAHA ALIH DAYA DALAM PROGRAM JAMINAN KESEHATAN NASIONAL (JKN) - Fanny Wiramijaya (2022)
The purpose of this research is to analyze the legal protection of workers in outsourcing business entities in the National Health Insurance Program (JKN). BPJS Kesehatan South Jakarta Branch Office, has conducted a compliance check with employers in registering their workers in the JKN program. It was found that several outsourcing companies have not registered their workers fully. This study uses a normative research method by examining Law No. 40 of 2004 concerning the National Social Security System, Law No. 24 of 2011 about the Badan Penyelenggara Jaminan Kesehatan(BPJS) and other regulations by using the theoretical approach of legal protection and the theory of law compliance enforcement as tool analysis. From this research it was found that, first, the protection of workers in outsourcing business entities in the JKN Program is divided into protection with the prevention category (prohibited) and protection with penalties (sanctions). Second, efforts to enforce registration compliance carried out by BPJS Kesehatan, including supervision and inspection, have been running effectively with a high registration compliance rate of around 88% after inspection efforts have been carried out.